Lesão por pressão em pacientes pediátricos : fluxograma de prevenção e sistematização do cuidado de enfermagem - Rodrigues, Carla Braga Oliveira (2018)
Introduction: The occurrence of pressure injury in children promotes pain and suffering, affects the life quality due to the psychosocial implications, represents greater hospital expenditure, increasing the length of hospital stay and the morbidity and mortality of pediatric patients. Organizing nursing activities in a systematized manner through instruments that contribute to the promotion of prevention and evaluation of children with pressure ulcer contributes to their safety and improves the quality of care. Objectives: To elaborate a risk flow chart and pressure ulcer prevention in pediatric patients; to develop an instrument for the systematization of nursing care for children with pressure ulcer based on Wanda Horta's Theory of Basic Human Needs and to validate the flow chart and the instrument with the nurses of a Public Hospital. Methodology: This is a validation study of technology, with a qualitative approach. The process took place in the following stages: 1) Identification of the phenomenon under study and clinical evidences, through the bibliographic review. 2) Elaboration of the risk flow chart and pressure ulcer prevention, and the instrument for Systematization of nursing care for this child. The structuring of these results used the content analysis of Bardin (2016). 3) Validation of contents by consensus among nurses through focal group technique. Results: The flowchart was validated and reconstructed through three categories: patient skin evaluation at admission; risk assessment: the Braden Q scale and the nursing prevention care according to the risk assessment; and the instrument through the content of risk factors and the basic human psychobiological requirements of oxygenation, hydration and electrolytic regulation, nutrition, elimination, sleep and rest, immobilization, locomotion, body mechanics and motility, cutaneous mucosal integrity, thermal regulation, neurological , vascular, painful, therapeutic and signs of wound infection. Products: pressure ulcer prevention flowchart for pediatric patients and Instrument of systematization of child care with pressure ulcer. Conclusion: The research allowed the collective reconstruction of a flow chart and an instrument for the evaluation of the child with pressure ulcer, based on the Basic Human Needs of Horta, which will subsidize the nurses in the prevention of pressure ulcer, as well as organize the work process with the pediatric patient.